2014
DOI: 10.5433/1679-0359.2014v35n1p505
|View full text |Cite
|
Sign up to set email alerts
|

Silage quality of Piata palisadegrass with palm kernel cake

Abstract: This study was developed to evaluate silage quality of Piata palisadegrass with palm kernel cake (Elaeis guineensis Jacq.). The experiment was carried out at the Federal Institute of Goiás State, Campus Rio Verde, in a completely randomized design with four treatments and five repetitions. The treatments consisted of Piata palisadegrass ensiled with palm kernel in the levels of 0, 5, 10 and 15% on a natural basis of the Piata palisadegrass. The material was minced, mixed, packed into experimental silos and ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
1
1
Order By: Relevance
“…These results corroborate the recommendations in the literature, as works carried out by Figueredo et al (2014) showed this relationship.…”
Section: Resultssupporting
confidence: 82%
“…These results corroborate the recommendations in the literature, as works carried out by Figueredo et al (2014) showed this relationship.…”
Section: Resultssupporting
confidence: 82%
“…The greatest lignin concentration in silages of monocropped Paiaguas palisadegrass (Table 6) is probably due to the greater fiber fractions of the grass. Figueredo et al (2014) observed lignin concentrations of 49.12 g kg −1 in silages of Piata palisadegrass in the exclusive form, but in the present study, values were above this level, with a mean value of 69.54 g kg −1 . Thus, these great concentration may limit the digestion of some tissues, not only by the negative effect of lignin on the digestion of cell wall components, but also by the arrangement of cells and by the large cell wall thickness (Oliveira et al, 2010).…”
contrasting
confidence: 80%
“…Several studies (Lukkananukool et al, 2013, Epifanio, Costa, Severiano, Bento, & Perim, 2014, Figueredo et al, 2014, Menezes et al, 2016, Guerra et al, 2016 fermentative process and the reduction of losses of tropical grass silages, among which the use of additives was highlighted. In this sense, the adsorbent additives, characterized by reducing or eliminating effluent production, may assume relevance in the production of forage grass silages with high moisture content.…”
Section: Introductionmentioning
confidence: 99%